Determinate dimension of numerical simulation model in submarine pipeline global buckling analysis. (15th March 2018) - Liu, Run; Li, Chengfeng
Abstract: Numerical simulation is an effective method to study the global buckling of submarine pipelines under high temperature and high pressure. The length of the pipeline model has a significant effect on the global buckling during the numerical simulation. This paper outlines the global buckling regularity of different pipes of various lengths and proposes a method to determine the pipe model length for the numerical simulation of pipe buckling by using theoretical analysis and the FEA method. A method of calculating the pipeline's critical length and upper-limit critical length is proposed based on the characteristics of the short pipe and long pipe. The numerical analysis results indicate that the global buckling amplitude of the short pipe increases with the length of the pipeline model. Therefore, the model length of a short pipeline in the numerical simulation should be equal to the actual length of the research object. In contrast, the buckling amplitude of pipes with a length greater than the critical length does not vary with the pipe length. Thus, the model length only needs to be equal to or slightly larger than the critical length. A method to determine the length of the pipe model for the numerical simulation of pipe buckling is proposed for various pipelines with different laying modes in practical engineering. Highlights: This paper outlines the significant effect of the pipeline length on the global buckling deformation and regularity. A method calculating the pipeline's critical length and upper-limit critical length is proposed based on the characteristics of the short pipeline and long pipeline. A method to determine the pipeline length for simulating pipeline buckling is proposed for pipelines with different laying modes in engineering.